1996
DOI: 10.1076/ejom.34.3.221.13033
|View full text |Cite
|
Sign up to set email alerts
|

The rodent granular convoluted tubule cell ? an update

Abstract: The cells of the granular convoluted tubule (GCT) of the rodent submandibular gland (SMG) are under complex developmental and multihormonal regulation. Recent findings indicate that GCT cells also synthesize transforming growth factor alpha (TGF-alpha), hepatocyte growth factor, erythroid differentiation factor, endothelin, and insulin-like growth factor, as well as several novel androgen-dependent proteins of unknown function. The GCTs of hypophysectomized mice provide a convenient model to study multihormona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…On the other hand, it is well established that the cells of the GCT in the rodent submandibular gland are unique in their functions: the cells synthesize biologically potent proteins such as transforming growth factor á (TGF-á), hepatocyte growth factor, erythroid differentiation factor, endothelin, insulin-like growth factor (Gresik et al 1996), and four major enzymes of the tissue kallikrein family, three of which convert prorenin to renin andÏor arginyl renin (Hosoi et al 1998). In this context, CgA may be a newly identified constituent of biologically potent proteins stored in the cells of the GCT and secreted into saliva.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it is well established that the cells of the GCT in the rodent submandibular gland are unique in their functions: the cells synthesize biologically potent proteins such as transforming growth factor á (TGF-á), hepatocyte growth factor, erythroid differentiation factor, endothelin, insulin-like growth factor (Gresik et al 1996), and four major enzymes of the tissue kallikrein family, three of which convert prorenin to renin andÏor arginyl renin (Hosoi et al 1998). In this context, CgA may be a newly identified constituent of biologically potent proteins stored in the cells of the GCT and secreted into saliva.…”
Section: Resultsmentioning
confidence: 99%
“…The submandibular gland of rodents possesses a specialized segment of the duct system, called the granular convoluted tubule [Letic-Gavrilovic and Abe, 1990;Gresik et al, 1996;Sato and Miyoshi, 1998;Kurabuchi et al, 2001]. The granular convoluted tubule in rodents secretes somatostatin, epidermal growth factor, nerve growth factor, kallikreins and CgA-LI as a new member [Letic-Gavrilovic and Abe, 1990;Kanno et al, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…Although many previous studies (reviewed in Gresik et al) (25,36) have shown that EGF protein and mRNA levels are correlated with each other and with the number of GCDs in rodents with experimentally reduced or absent GCD, or experimentally increased GCD, the findings of the current study indicate that the molecular mechanism controlling EGF secretion is independent of that controlling GCD growth. This idea regarding independent developmental and secretory regulatory pathways has been previously suggested by Siminoski et al (37), who proposed that submandibular NGF and EGF could be controlled by similar cellular or molecular mechanisms independent of the regulation of generalized growth responses.…”
Section: Figmentioning
confidence: 35%
“…These results may be explained by the ability of BCA to induce proliferation at small concentrations lower than 0.1 to 10 μM, whereas a similar proliferative capacity of estradiol is achieved at 0.2 or 0.3 μM on MCF7 cells in vitro (25)(26)(27)(28). Additionally, the results in the current study may be attributed to the effect of BCA and E2 on DNA synthesis.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation